2021
DOI: 10.3399/bjgp.2021.0275
|View full text |Cite
|
Sign up to set email alerts
|

Building the case for the use of gut feelings in cancer referrals: perspectives of patients referred to a non-specific symptoms pathway

Abstract: BackgroundGut feelings may be useful when dealing with uncertainty, which is ubiquitous in primary care. Both patients and GPs experience this uncertainty but patients’ views on gut feelings in the consultation have not been explored.AimTo explore patients’ perceptions of gut feelings in decision making, and to compare these perceptions with those of GPs.Design and settingQualitative interviews with 21 patients in Oxfordshire, UK.MethodPatients whose referral to a cancer pathway was based on their GP’s gut fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Patients' impressions of the way GPs used their own gut feelings in clinical decision-making were similar to those reported by GPs. (25) Our study found that some Belgian patients seemed to be more reticent about informing their GP of their gut feelings than Dutch patients. This might be explained by cultural differences as indications for similar differences were found in an earlier study.…”
Section: Comparison With Existing Literaturementioning
confidence: 50%
See 2 more Smart Citations
“…Patients' impressions of the way GPs used their own gut feelings in clinical decision-making were similar to those reported by GPs. (25) Our study found that some Belgian patients seemed to be more reticent about informing their GP of their gut feelings than Dutch patients. This might be explained by cultural differences as indications for similar differences were found in an earlier study.…”
Section: Comparison With Existing Literaturementioning
confidence: 50%
“…In a previous study that examined how patients perceived the role of GPs’ gut feelings in clinical decision making, some patients described their own gut feeling as ‘something is wrong’. 25 They explained that their gut feeling was based on the knowledge of their body and what was normal for them. This gut feeling led to action in the form of seeking medical help.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of recent BJGP articles, our group has explored GPs' gut feelings in relation to the decision to investigate for cancer. [1][2][3] Our first article, a systematic review and metaanalysis, indicated that GPs' gut feelings represent a rapid summing-up of multiple, often subtle, verbal and non-verbal cues noted in the consultation. This summingup could lead to a sense that a patient was seriously unwell, and when GPs had this gut feeling the odds of a cancer diagnosis were four times higher than when no gut feeling was recorded.…”
Section: Introductionmentioning
confidence: 99%
“…1 Two interview studies then explored gut feelings with GPs and patients, respectively, who had either made referrals or been referred for cancer investigation. 2,3 Both groups perceived gut feeling was gradually honed with increasing clinical experience and personal experience of the patient. Patients said that they thought the 'thorough GP' would validate this short-cut in clinical reasoning through further evidence gathering.…”
Section: Introductionmentioning
confidence: 99%